2006
DOI: 10.1016/j.jcomdis.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of early speech sound disorders: A factor analytic study

Abstract: The goal of this study was to classify children with speech sound disorders (SSD) empirically, using factor analytic techniques. Participants were 3-7-year olds enrolled in speech/language therapy (N = 185). Factor analysis of an extensive battery of speech and language measures provided support for two distinct factors, representing the skill dimensions of articulation/phonology and semantic/ syntactic skills. To validate these factors, 38 of the children were followed to school age to re-evaluate speech and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 53 publications
1
44
0
7
Order By: Relevance
“…Participants were recruited from the clinical practices of speech and language pathologists at community speech and hearing centers or in private practice in the greater Cleveland area. They were part of an ongoing study of the genetics of SSD 36,37 and were tested between 1995 and 2004.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited from the clinical practices of speech and language pathologists at community speech and hearing centers or in private practice in the greater Cleveland area. They were part of an ongoing study of the genetics of SSD 36,37 and were tested between 1995 and 2004.…”
Section: Participantsmentioning
confidence: 99%
“…These measures have adequate validity and have been used in prior studies by our group. 21,23,36,37,54 Nonverbal IQ-To assess nonverbal intelligence, PIQ was measured using the WPPSI-R. 41 Outcome Measures-The Test of Early Reading Ability-2 (TERA) was used to measure pre-academic reading readiness. 42 The TERA measures the ability to construct meaning from printed symbols, knowledge of the alphabet, and understanding of the conventions of written language (print concept knowledge) in children ages 3 to 9 years.…”
Section: Speech and Languagementioning
confidence: 99%
“…Studies have also shown a variety of speech and language disorders aggregate in firstdegree family relatives of children diagnosed with CAS (Lewis et al, 2004;Lewis et al, 2006). A similar pattern of family aggregation has been observed for speech-disordered children without CAS (Lewis et al, 2004).…”
mentioning
confidence: 53%
“…If the proper treatment of these problems starts in due time, they can be corrected because psycholinguistic automatisms are not consolidated in young children [2].…”
Section: The Challenges Of Speech Disorder Therapymentioning
confidence: 99%